The dead of night [compact disc, unabridged] - Lerangis, Peter (39 clues. Cahills vs. Vespers, 2011)
When seven members of his family were kidnapped by the Vespers thirteen-year-old Dan Cahill knew he was in for the fight of his life. He knew he was up against an impossibly powerful enemy. And Dan knew the odds were that some of his family members wouldn't make it. But even as Dan steels himself to accept these facts, the unthinkable happens. The Vespers capture a blameless bystander, Dan's best friend Atticus. With an innocent life on the line, Dan kicks off a frantic hunt that will take him from the back alleys of Prague to the rock caves of Turkey. But Dan better find Atticus fast. If he doesn't, his best friend will surely die.